The path of critical editing in the life of Juan Francisco Sans (Mayéutica Revista Científica de Humanidades y Artes, 2023)
As part of my undergraduate studies at the School of Arts of the Universidad  Central de Venezuela, I had the opportunity to meet and share knowledge with Juan Francisco Sans, who was also the tutor for my degree project, an experience in which he introduced me to critical edition. This essay is an approximation to that fruitful personal encounter with all the imprint it has had on my professional development.
Keywords: Juan Francisco Sans; Universidad Central de Venezuela; Musicology; Centro de Documentación e Investigaciones Acústico Musicales; critical music edition